Leverage points for meaningful participatory governance: lessons from the Tsitsa River catchment, South Africa - Fry, Anthony St Leger (Rhodes University, Faculty of Science, Institute for Water Research)
South Africa underwent the renowned transition into a representative multiracial democracy in 1994. While there has been notable progress in many developmental aspects of South African society, many inherited dilemmas persist, and myriad novel ones are emerging. In land and water governance, the nascent institutions do not reflect the visions laid out in the pioneering and substantive legislation, policies, and guidelines generated in the post-1994 period. Unaddressed dilemmas include widespread failures in local water governance, persistent inequality of access to land and water, poor or non-existent service delivery in rural areas, underdeveloped institutions for integrated and inclusive water resource management, and pernicious divisions between institutions. Overcoming these challenges, which are embedded in complex social-ecological systems across South Africa, will require the collaborative effort of diverse actors from different levels and sectors of society. So how do we foster meaningful participation in ways that are not tyrannical, tokenistic, or manipulative? How do we build local institutions that make sense in the broader political system and in the lives of rural residents? How do we support institutions that meaningfully include diverse voices and enable tangible development outcomes? This thesis explores these questions as part of the Tsitsa Project, a transdisciplinary landscape management project working in the Tsitsa River Catchment (TsRC) in the rural parts of the Eastern Cape province of South Africa. Based on the valuable water resources, severe ecosystem degradation, overlapping traditional and democratic governance systems, and impoverished population, the TsRC is a worthwhile candidate for in-depth study paired with innovative efforts towards systemic development. The single place-based case study approach drew on systems thinking within an evolving transdisciplinary methodology. Qualitative data were collected through extended fieldwork and analysed through an adaptive and iterative approach. Governance mapping elucidated the multiple levels of governance, and a systemic analysis explored meaningful participation at the local level through causal diagramming and observation-based narratives. From the findings, a synthetic analysis identified high leverage points to enable participatory governance interventions to have more sustained impacts. Governance manifestations in the TsRC generally align with existing descriptions of the fractures and associated dilemmas across South Africa, with the added complexities of being a rural landscape in which democratic and traditional governance systems overlap and interact. Local participatory institutions need to endure the broader instability and dysfunction. Interventions must, therefore, be oriented towards trust building and shared understanding while using more practical interventions that provide tangible outcomes, enable in-practice capacity development, and support platforms for all actors to experience and practice meaningful participation together. This thesis aims to unearth the lessons that one small rural catchment might hold for the governance of complex, contested land and for water governance contexts more broadly.
Keywords: Watershed management -- South Africa -- Eastern Cape -- Citizen participation; Political participation -- South Africa; Twelve leverage points; Transdisciplinarity; Socio-ecological system